In situ activation of benzyl alcohols with XtalFluor-E: formation of 1, 1-diarylmethanes and 1, 1, 1-triarylmethanes through Friedel–Crafts benzylation. Issue 8 (16th January 2015) - Desroches, Justine; Champagne, Pier Alexandre; Benhassine, Yasmine; Paquin, Jean-François
Abstract : The Friedel–Crafts benzylation of arenes using benzyl alcohols activated in situ with XtalFluor-E is described. A wide range of 1, 1-diarylmethanes and 1, 1, 1-triarylmethanes were prepared under simple and mild conditions, without the need for a transition metal or a strong Lewis acid. Abstract : The Friedel–Crafts benzylation of arenes using benzyl alcohols activated in situ with XtalFluor-E is described. A wide range of 1, 1-diarylmethanes and 1, 1, 1-triarylmethanes were prepared under experimentally simple and mild conditions, without the need for a transition metal or a strong Lewis acid. Notably, the reactivity observed demonstrates the potential of XtalFluor-E to induce C–OH bond ionization and SN 1 reactivity of benzylic alcohols.